2019
DOI: 10.1016/j.trc.2019.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Real-time city-scale ridesharing via linear assignment problems

Abstract: In this paper, we propose a novel, computational efficient, dynamic ridesharing algorithm. The beneficial computational properties of the algorithm arise from casting the ridesharing problem as a linear assignment problem between fleet vehicles and customer trip requests within a federated optimization architecture. The resulting algorithm is up to four times faster than the state-of-the-art, even if it is implemented on a less dedicated hardware, and achieves similar service quality. Current literature showca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
174
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 160 publications
(178 citation statements)
references
References 58 publications
3
174
0
1
Order By: Relevance
“…In the Brainport simulations, we generate a fleet of 100 virtual vehicles serving between 360 and 1440 user requests during 1 hour of service. Vehicles are assigned to requests every 10 seconds: [8] showed that such frequency for batch assignment provides an optimum trade-off between level of service and computation time. We have several speed cameras connected to the oneM2M IoT platform which provide traffic events every 5 min.…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Brainport simulations, we generate a fleet of 100 virtual vehicles serving between 360 and 1440 user requests during 1 hour of service. Vehicles are assigned to requests every 10 seconds: [8] showed that such frequency for batch assignment provides an optimum trade-off between level of service and computation time. We have several speed cameras connected to the oneM2M IoT platform which provide traffic events every 5 min.…”
Section: Simulationsmentioning
confidence: 99%
“…Ridesharing is typically solved in a centralised fashion across the whole vehicle fleet and across customers, as to minimise the total travel time of the operating vehicles, while taking into account the customer pref-erences (pickup and drop-off times, whether sharing is desired or not, etc.) [8,7,3]. Ridesharing emerged in the past few decades amongst the shared-mobility services as a means to limit traffic congestion and achieve environmental benefits.…”
Section: Introductionmentioning
confidence: 99%
“…In Simonetto et al (2019), it is highlighted that linear assignments can perform as good as more elaborated assignments, when run at a high enough sampling rate. Simonetto et al (2019) shows that optimization-based approaches for on-demand ridesharing can provide a high level of service while limiting the growth of the fleet size. Specifically, it is shown that 98% of the current trip demand in Manhattan, available via the New York Taxi dataset (NYC Taxi and Limousine Commission dataset 2019), can be satisfied with only 20% of the current taxi fleet (Alonso-Mora et al 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…In order to evaluate advantages and limitation of the Cooperative and Competitive models, we compare them with a Centralized model, obtained by adapting the work of Simonetto et al (2019) to the multi-company setting. Hence, a suitable proxy for an efficient Centralized model for multi-company ridesharing systems is as follows: (i) the system collects batches of customer requests for a given time period, e.g., 10 s, (ii) the companies compute the costs for inserting requests in each vehicle route, by solving a DARP problem, (iii) those costs are shared with the broker, (iv) the broker solves the Linear Assignment Problem (LAP) to optimality and sends the updated assignments of vehicles to requests (v) the broker adopts a rebalancing strategy for the unserved requests, which means running steps (i)-(iv) with loose time constraints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation